2019
DOI: 10.3389/fpls.2019.00623
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis Lectin Receptor Kinase LecRK-I.8 Is Involved in Insect Egg Perception

Abstract: Plants induce defense responses after insect egg deposition, but very little is known about the perception mechanisms. In Arabidopsis thaliana , eggs of the specialist insect Pieris brassicae trigger accumulation of reactive oxygen species (ROS) and salicylic acid (SA), followed by induction of defense genes and localized necrosis. Here, the involvement of the clade I L-type lectin receptor kinase LecRK-I.8 in these responses was studied. Expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 59 publications
(115 reference statements)
1
47
0
Order By: Relevance
“…Oviposition or EE application trigger similar SA accumulation, ROS production, cell death, and defense gene expression in Arabidopsis ( Little et al, 2007 ; Bruessow et al, 2010 ; Gouhier-Darimont et al, 2013 ; Gouhier-Darimont et al, 2019 ; Figure 1—figure supplement 1 ). In addition, we recently showed that the receptor-like kinase LecRK-I.8 is an early component of egg-induced signaling responses ( Gouhier-Darimont et al, 2019 ). To test whether PCs can mimic these responses in a LecRK-I.8-dependent manner, Arabidopsis Col-0 and a T-DNA knock-out lecrk-I.8 mutant were exposed to oviposition by P. brassicae butterflies, or treated with EE and different synthetic PCs.…”
Section: Resultsmentioning
confidence: 96%
“…Oviposition or EE application trigger similar SA accumulation, ROS production, cell death, and defense gene expression in Arabidopsis ( Little et al, 2007 ; Bruessow et al, 2010 ; Gouhier-Darimont et al, 2013 ; Gouhier-Darimont et al, 2019 ; Figure 1—figure supplement 1 ). In addition, we recently showed that the receptor-like kinase LecRK-I.8 is an early component of egg-induced signaling responses ( Gouhier-Darimont et al, 2019 ). To test whether PCs can mimic these responses in a LecRK-I.8-dependent manner, Arabidopsis Col-0 and a T-DNA knock-out lecrk-I.8 mutant were exposed to oviposition by P. brassicae butterflies, or treated with EE and different synthetic PCs.…”
Section: Resultsmentioning
confidence: 96%
“…Localized cell death was also observed in Arabidopsis thaliana after P. brassicae egg-laying (Little et al, 2007;Gouhier-Darimont et al, 2019); however, the response in this plant species is less strong and specific compared to Brassica spp., being A. thaliana not a foodplant for these butterflies (Harvey et al, 2007).…”
Section: Egg-induced Direct Plant Responsesmentioning
confidence: 93%
“…This protein seems to play a key role in early signal transduction steps by controlling several responses to P. brassicae egg-laying. The authors demonstrated that a lipidic fraction from P. brassicae eggs triggers localized cell death and that this response is significantly attenuated in lecrk-I.8 mutant plants, suggesting that LecRK-I.8 is involved in the sensing of an egg-derived lipidic compound (Gouhier-Darimont et al, 2019).…”
Section: Egg-derived Elicitorsmentioning
confidence: 99%
“…However, not only the JA pathway is activated after spider mite infestation. The induction of both JA and SA pathways has been reported in spider mite infested thale cress [42,64,70], tomato [44,47], citrus [40,43,80] and pepper [46], among other plant species. Moreover, He et al [81] also reported the accumulation of SA and conjugated-SA forms induced by spider mite attack in bean (Phaseolus vulgaris) leaves but the JA content was not analyzed in this study.…”
Section: Inducible Defenses: Early Signalling Eventsmentioning
confidence: 99%
“…They act as active participants in the recognition of HAMPs derived from phytophagous insects to trigger defense pathways. Some PRRs have been identified in plants interacting with certain lepidopteran and aphid species [60][61][62][63][64]. In contrast, the information on PRRs associated with the recognition of other insect species is very limited.…”
Section: Inducible Defenses: Plant Perceptionmentioning
confidence: 99%